Karakteristik Fisik, Kimia dan Tingkat Kesukaan Keripik yang Disubtitusi Dengan Tepung dan Bubur Daun Katuk (Sauropus Androgynus) - Hayria; Siti Tamaroh Cahyono Murti (Journal of Food and Agricultural Technology, 2026)
One of the plants that is quite famous is katuk leaves. Katuk leaf plants by the community are only used as vegetable food and food coloring. Therefore, the effort that can be done is through a processing process, namely making katuk leaves into flour and katuk leaf pulp so that they are easily mixed in other ingredients and then processed into products in the form of chips. The purpose of this study was to determine and determine the effect of adding katuk leaf flour and katuk leaf pulp on physical and chemical properties and the level of preference for katuk leaf chips. This research was conducted by making chips made from wheat flour substituted with flour and katuk leaf pulp using a Completely Randomized Design (CRD) with research factors substitution of 20%, 25% and 30% of katuk leaf flour and pulp with physical analysis of color and texture, Chemical analysis of selected treatment included total phenolic content, water, ash, fat, protein, and carbohydrate as well as preference test. The data were tested using SPSS and if they were significantly different, the Duncan's Multiple Range Test continued with a significant level of 0.05. The results showed that 20% katuk leaf flour substitution chips and 25% katuk leaf pulp were the treatments chosen by the panelists. The physical characteristics tested include L, a*, b* and texture. Chemical characteristics include analysis of total phenolic content, which is 242.6 mg GAE/g and 66.3 mg GAE/g, water content is 5.25 %w/w and 5.85 %w/w, ash content is 1.47 %w/w. and 1.30 %w/w, fat content of 2.46 %w/w and 8.08%w/w, protein content of 8.77 %w/w and 8.10%w/w, carbohydrate content of 80.24 %w/w and 76.62 %w/w and favored by the panelists.